2020
DOI: 10.1590/1678-5150-pvb-6147
|View full text |Cite
|
Sign up to set email alerts
|

Companion psittacine birds as reservoir of gentamicin and vancomycin-resistant Enterococcus spp.

Abstract: Enterococcus are recognized worldwide as significant nosocomial agents that have been continuously envolving to adapt to different niches and acquire resistance to several antibiotic classes. Vancomycin and gentamicin-resistant strains of E. faecalis and E. faecium have been associated with nosocomial human infections. Some epidemiological studies suggest the participation of pets as reservoirs of vancomycin and gentamicin-resistant Enterococcus strains. However, the role of companion birds as reservoirs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…22 E. faecalis isolates obtained in our study were found to be sensitive to vancomycin at a rate of 95.5%. Cabral et al (2020) investigated the distribution of Enterococcus species, their resistance to gentamicin and vancomycin in their study on Psittacine (parrot-like, curved-billed birds) birds in Brazil. For this purpose, they took samples from 126 birds and isolated Enterococcus species (E. hirae, E. faecium, E. phoeniculicola, E. faecalis, E casseliflavus and E. gallinarum) at a rate of 26.9%, similar to our study (29%).…”
Section: Discussionmentioning
confidence: 99%
“…22 E. faecalis isolates obtained in our study were found to be sensitive to vancomycin at a rate of 95.5%. Cabral et al (2020) investigated the distribution of Enterococcus species, their resistance to gentamicin and vancomycin in their study on Psittacine (parrot-like, curved-billed birds) birds in Brazil. For this purpose, they took samples from 126 birds and isolated Enterococcus species (E. hirae, E. faecium, E. phoeniculicola, E. faecalis, E casseliflavus and E. gallinarum) at a rate of 26.9%, similar to our study (29%).…”
Section: Discussionmentioning
confidence: 99%
“…Animals, particularly wildlife ones, are believed to be the source of 70% of all emerging infections ( Ahmed et al ., 2007 ). Although in recent years special attention has been paid to the role of animals as sentinels and spreaders of AMR, few studies have evaluated the occurrence of AMR bacteria in wild and exotic pets ( Chiacchio et al ., 2016 ; Dias et al ., 2018 ; Cabral et al ., 2020 ; Marques et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MALDI-TOF MS system is used successfully for precise identification of bacteria isolated from various types of specimens (Stępień-Pyśniak et al, 2017;Davies et al, 2016b;Cabral et al, 2020). Therefore, species identification would improve timeliness and reduce isolate identification costs in clinical bacteriology laboratories (Cherkaoui et al, 2010).…”
Section: Introductionmentioning
confidence: 99%